Hubungan Selfcare dengan Kualitas Hidup pada Pasien Diabetes Melitus Tipe II - I Gede Agus Surya Raditya; I Made Mertha; Ni Made Wedri; I Gusti Ketut Gede Ngurah (Jurnal Gema Keperawatan, 2022)
Diabetes mellitus (DM) is a chronic disease in form metabolic disorders characterized by an increase in blood sugar levels more than normal limit. According to data on people with diabetes mellitus at the UPTD Public Health Center, North Kuta District, in 2019 there were 66 cases of people with diabetes mellitus served. In 2020 there was an increase from previously only 66 cases diabetes were served, increasing to 328 cases of diabetics who were served at the puskesmas. Meanwhile, in 2021 number cases of people with diabetes being served was 497 cases. This study aim to determine relationship between self care and quality of life in patients with diabetes mellitus at the UPTD Puskesmas Kuta Utara in 2022. Study used a research design using an observational or non-experimental design using a cross-sectional approach. Results of study using the chi-square test obtained the asymmp.sig (2-sided) value of 0.002. Because the value of asymp.sig (2-sided) is 0.000 0.05. It can be concluded that relationship between self care and quality of life in patients with type II diabetes mellitus with a contingency coefficient (CC) of 0.513 indicates a moderate relationship between self care variables and quality of life. the researchers recommend that patients always pay attention to health conditions and food, routinely carry out medication and at the Puskesmas to continue the program and educate patients with diabetes mellitus.